Endoplasmic reticulum stress and ubiquitin-proteasome system impairment in natural scrapie - Lozada Ortiz, Jenny; Betancor, Marina; Pérez Lázaro, Sonia; Bolea, Rosa; Badiola, Juan J.; Otero, Alicia (Frontiers in Molecular Neuroscience, 2023)
Chronic accumulation of misfolded proteins such as PrPSc can alter the endoplasmic reticulum homeostasis triggering the unfolded protein response (UPR). In this pathogenic event, the molecular chaperones play an important role. Several reports in humans and animals have suggested that neurodegeneration is related to endoplasmic reticulum stress in diseases caused by the accumulation of misfolded proteins. In this study, we investigated the expression of three endoplasmic reticulum stress markers: PERK (protein kinase R-like endoplasmic reticulum kinase), BiP (binding immunoglobulin protein) and PDI (Protein Disulfide Isomerase). In addition, we evaluated the accumulation of ubiquitin as a marker for protein degradation mediated by the proteasome. These proteins were studied by in brain tissues of sheep affected by scrapie in clinical and preclinical stages of the disease. Results were compared with those observed in healthy controls. Scrapie-infected sheep showed a significant higher levels of PERK, BiP/Grp78 and PDI than healthy animals. As we observed before in models of spontaneous prion disease, PDI was the most altered ER stress marker between scrapie-infected and healthy sheep. Significantly increased intraneuronal and neuropil ubiquitinated deposits were observed in certain brain areas in scrapie-affected animals compared to controls. Our results suggest that the neuropathological and neuroinflammatory phenomena that develop in prion diseases cause endoplasmic reticulum stress in brain cells triggering the UPR. In addition, the significantly higher accumulation of ubiquitin aggregates in scrapie-affected animals suggests an impairment of the ubiquitin-proteasome system in natural scrapie. Therefore, these proteins may contribute as biomarkers and/or therapeutic targets for prion diseases.